Interacting effects of particulate pollution and cold temperature on cardiorespiratory mortality in Scotland. Issue 3 (10th October 2007) - Carder, M; McNamee, R; Beverland, I; Elton, R; Van Tongeren, M; Cohen, G R; Boyd, J; MacNee, W; Agius, R M
Abstract : Objectives: To determine whether the effect of black smoke on cardiorespiratory mortality is modified by cold temperatures. Methods: Poisson regression models were used to investigate the relationship between lagged black smoke concentration and daily mortality, and whether the effect of black smoke on mortality was modified by cold temperature for three Scottish cities from January 1981 to December 2001. Main results: For all-cause respiratory and non-cardiorespiratory mortality, there was a significant association between mortality and lagged black smoke concentration. Generally the maximum black smoke effect occurred at lag 0, although these estimates were not statistically significant. A 10 μgm −3 increase in the daily mean black smoke concentration on any given day was associated with a 1.68% (95% CI 0.72 to 2.65) increase in all-cause mortality and a 0.43% (95% CI −0.97 to 1.86), 5.36% (95% CI 2.93 to 7.84) and 2.13% (95% CI 0.82 to 3.47) increase in cardiovascular, respiratory and non-cardiorespiratory mortality, respectively, over the ensuing 30-day period. The effect of black smoke on mortality did not vary significantly between seasons (cool and warm periods). For all-cause, cardiovascular and non-cardiorespiratory mortality the inclusion of interaction terms did not improve the models, although for all-cause and non-cardiorespiratory mortality there was a suggestion for interaction between temperature and recent black smoke exposure. Conclusions: The results of this study suggested a greater effect of black smoke on mortality at low temperatures. Since extremes of cold and particulate pollution may coexist, for example during temperature inversion, these results may have important public health implications.